Distribution of Leadership in Higher Institution; A Case Study at Tribakti University, Kediri - Rochimah, Nur; Mustamir, Ahmad Khoirul (IAIN Manado, 2024)
Distribution of Leadership in Higher Institution; A Case Study at Tribakti University, Kediri. This study focuses on the distribution of leadership in Lirboyo Islamic Boarding School, Kediri City, to the scope of UIT Kediri. Charismatic leadership shows modern leadership, which certainly impacts the shift from the pesantren culture to the academic culture (campus). This study uses a qualitative-phenomenological method, extracting data from interviews with key informants and documenting studies according to focus and documentation. The data obtained were compiled and analyzed according to the research focus. The results of this study indicate that since the establishment of the Tribakti Islamic University (UIT), the practice of distribution of leadership at UIT Kediri is a reflection of the courage of PP Lirboyo's caregivers in carrying out leadership transformation. The impact is the creation of academic culture in the UIT Kediri environment by not eliminating the treasures of the pesantren. It can be concluded that the practice of leadership transformation and distribution of leadership at UIT Kediri is not total or total. For example, in developing and accepting human resources at UIT Kediri, the Lirboyo community must involve the Lirboyo community and determine the formation of leaders